Peran Kecerdasan Buatan dalam Inovasi Bisnis: Studi Kasus Penerapan AI di Sektor Keuangan dan E-Commerce - Angel Sri Monika Sijabat; Grace Stela Zane Simamora; Leoni Geraldin Br. Simamora (Perkumpulan Konsultan Manajemen Pendidikan Indonesia (PKMPI), 2023)
Artificial intelligence (AI) has become an important component in driving digital transformation and business model innovation in various industry sectors. This research aims to comprehensively examine the role and impact of AI in the finance and e-commerce sectors as two of the most dynamic areas of technology adoption. Using a desk study approach of ten recent scientific journals, this research evaluates the contribution of AI in improving operational efficiency, decision-making accuracy, customer service personalization, and financial inclusion through digitization. The results show that AI can drive risk management efficiency, accelerate digital financial services, and improve user experience in e-commerce through automation and intelligent recommendation systems. However, the implementation of AI is also faced with ethical challenges, such as data privacy issues, algorithm bias, and limited adequate regulations. This research also highlights the importance of strengthening human resource competencies and supporting MSME players in facing the AI-based business era. Thus, AI has the potential to be the main driver of innovation and business sustainability in the future if integrated ethically, inclusively, and strategically